2007
DOI: 10.1161/circulationaha.106.681320
|View full text |Cite
|
Sign up to set email alerts
|

Long-Term Impact of Diabetes and Its Comorbidities in Patients Undergoing Isolated Primary Coronary Artery Bypass Graft Surgery

Abstract: Background— The objective of this study was to identify the impact of diabetes and related comorbidities, namely chronic renal failure, peripheral vascular disease, and low ejection fraction (<35%), on long-term survival of patients undergoing coronary artery bypass graft surgery. Methods and Results— A unicenter study was conducted on 9125 survivors of isolated coronary artery bypass graft surgery between 199… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
52
1

Year Published

2008
2008
2020
2020

Publication Types

Select...
6
4

Relationship

1
9

Authors

Journals

citations
Cited by 64 publications
(54 citation statements)
references
References 27 publications
1
52
1
Order By: Relevance
“…1,2 Moreover, patients with DM experience poorer outcomes from these events, including a greater risk of death or recurrent myocardial infarction (MI). 3,4 Among patients undergoing coronary stenting, patients with DM also have a higher risk for stent thrombosis. 5 Part of the effect of DM may be explained by the contribution of insulin resistance and hyperglycemia to a prothrombotic state including direct effects on platelet function, both adhesion and aggregation, resulting in hyperreactivity.…”
mentioning
confidence: 99%
“…1,2 Moreover, patients with DM experience poorer outcomes from these events, including a greater risk of death or recurrent myocardial infarction (MI). 3,4 Among patients undergoing coronary stenting, patients with DM also have a higher risk for stent thrombosis. 5 Part of the effect of DM may be explained by the contribution of insulin resistance and hyperglycemia to a prothrombotic state including direct effects on platelet function, both adhesion and aggregation, resulting in hyperreactivity.…”
mentioning
confidence: 99%
“…Although recent literature has shown that perioperative survival is improved with glycemic control (whether tight or liberal) long-term data are scarce [14,15,[23][24][25][26][27][28][29][30][31]. Diabetic patients with coronary artery disease reputedly have worse long-term outcomes than nondiabetic patients [15].…”
Section: Commentmentioning
confidence: 99%
“…[8][9][10][11][12][13] The diabetic population represents more than 38% of patients undergoing cardiac surgery procedures, especially coronary revascularisation. 14 It has been assumed that the greater surgical risk associated with diabetes mellitus might be a consequence of an altered inflammatory response to CPB, 15 which is characterised by increased secretion of cytokines (interleukin-6 [IL-6]) and tumour necrosis factor-alpha (TNF-α), oxidative stress 16,17 and endothelial dysfunction, 8,18 especially in the mesenteric vasculature.…”
Section: Introductionmentioning
confidence: 99%